The Effect of Consumer Multifactorial Gender and Biological Sex on the Evaluation of Cross‐Gender Brand Extensions. Issue 9 (23rd July 2013) - Ulrich, Isabelle
ABSTRACT: Introducing cross‐gender brand extensions—masculine or feminine brands that extend to the opposite gender—is a growing trend on the marketplace, though not always a successful one. This research examines the effect of consumer multifactorial gender and biological sex on consumers' evaluation of cross‐gender brand extensions. The influence of gender role attitudes is demonstrated: consumers with traditional gender attitudes are significantly more reluctant to accept these extensions than consumers with more liberal attitudes. Hence the extensions have a negative impact on the subsequent attitude of the former group toward the parent brand, contrary to their effect on more egalitarian consumers. No significant impact of the consumer's biological sex, gender identity, or sexual orientation is identified. The theoretical and managerial implications of these findings for the development of cross‐gender brand extensions are discussed.